2014
DOI: 10.1063/1.4896147
|View full text |Cite
|
Sign up to set email alerts
|

Structural control of elastic moduli in ferrogels and the importance of non-affine deformations

Abstract: One of the central appealing properties of magnetic gels and elastomers is that their elastic moduli can reversibly be adjusted from outside by applying magnetic fields. The impact of the internal magnetic particle distribution on this effect has been outlined and analyzed theoretically. In most cases, however, affine sample deformations are studied and often regular particle arrangements are considered. Here we challenge these two major simplifications by a systematic approach using a minimal dipole-spring mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 58 publications
2
67
0
Order By: Relevance
“…However, the nature of the mechanical response and other characteristic material properties can strongly depend on the spatial distribution of the magnetic particles within the sample. 1,31,[44][45][46][47][48][49][50][51] Typical particle diameters range from nano-to micrometers and thus involve an intermediate, i.e., mesoscopic length scale. Finally, for rubbery substances, the fact that the materials are elastic mainly results from the entropic properties of the single crosslinked polymer chains and is therefore of molecular microscopic origin.…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature of the mechanical response and other characteristic material properties can strongly depend on the spatial distribution of the magnetic particles within the sample. 1,31,[44][45][46][47][48][49][50][51] Typical particle diameters range from nano-to micrometers and thus involve an intermediate, i.e., mesoscopic length scale. Finally, for rubbery substances, the fact that the materials are elastic mainly results from the entropic properties of the single crosslinked polymer chains and is therefore of molecular microscopic origin.…”
Section: Introductionmentioning
confidence: 99%
“…41 Ferrofluids 42 and ferrogels [43][44][45] (for a recent review see Ref. 46) with magnetic particles provide further prominent examples of smart materials where anisotropic particles are involved.…”
Section: Introductionmentioning
confidence: 99%
“…This may be exploited in constructing novel damping devices [10] and vibrational absorbers [11]. Several theoretical studies have shown that the internal spatial particle distribution plays a qualitative role for this effect [12][13][14][15]. Furthermore, applying time-dependent external magnetic fields can induce deformations, which makes the materials candidates for the use as soft actuators [5,16,17].…”
Section: Introductionmentioning
confidence: 99%